1998
DOI: 10.1007/s003810050305
|View full text |Cite
|
Sign up to set email alerts
|

"No Allogeneic Blood Transfusion" protocol for the surgical correction of craniosynostoses

Abstract: Improved anesthesiological and surgical care has resulted in a progressively declining need for allogeneic blood transfusion. In infants with craniosynostosis, however, allogeneic blood transfusion is still performed as a routine procedure. In the present paper, the authors describe a protocol they have devised with the aim of limiting or even avoiding allogeneic blood transfusion even in very young patients, consequently avoiding the risks of infective or immunologic reactions associated with the procedure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 64 publications
(52 reference statements)
1
25
0
3
Order By: Relevance
“…28 In the first clinical experience, Velardi and colleagues developed a protocol to minimize autologous blood transfusion that included treating patients preoperatively with EPO, ANH, and intraoperative blood cell salvage. 35 Hemoglobin concentrations were increased in patients treated with EPO for at least 2 weeks. Krajewski and colleagues administered EPO 3 weeks, 2 weeks, and 1 week preoperatively and used Cell Saver intraoperatively; there was a marked increase in preoperative hematocrit and lower transfusion rates.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…28 In the first clinical experience, Velardi and colleagues developed a protocol to minimize autologous blood transfusion that included treating patients preoperatively with EPO, ANH, and intraoperative blood cell salvage. 35 Hemoglobin concentrations were increased in patients treated with EPO for at least 2 weeks. Krajewski and colleagues administered EPO 3 weeks, 2 weeks, and 1 week preoperatively and used Cell Saver intraoperatively; there was a marked increase in preoperative hematocrit and lower transfusion rates.…”
Section: Discussionmentioning
confidence: 94%
“…19 The transfusion-minimizing protocol reported by Velardi and colleagues included Cell Saver use. 35 Dahmani and coauthors found a significant decrease in the amount of homologous blood transfused in the continuous autotransfusion group. 5 Fearon described a series of patients who received autologous recycled blood and found a rate of allogenic transfusion of only 18% with no complications associated with the use of cell salvage.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Использование гемо-дилюции, когда расчетное количество донорской крови заменяется препаратами гидроксиэтилкрахмала (рефор-таном, волювеном), приводит к развитию острой или подострой анемии, снижению вязкости крови, при этом сохраняется тканевая перфузия. Применение у детей раннего возраста (до 1 года) не рекомендовано, но тем не менее процедура проводится и дает положительный результат в виде уменьшения объема гемотрансфузии, особенно при реконструктивных операциях для коррек-ции краниосиностозов [16]. Отрицательным моментом является развитие и прогрессирование гипокоагуляции, требующей динамического контроля для профилактики и коррекции нарушений коагуляционного гемостаза [17].…”
Section: педиатрическая фармакологияunclassified